2019
DOI: 10.1177/0022219419882648
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Linguistic Skills Underlying Word Reading and Spelling Difficulties in Chinese Adolescents With Dyslexia

Abstract: The present study investigated the co-occurrence of word reading and spelling difficulties for Chinese first language (L1) and English second language (L2) and the role of morphological awareness in word reading and spelling ability across two languages. A total of 110 Hong Kong Chinese-speaking students in Grade 7, including 55 adolescents with dyslexia (28 males, mean age = 152.11 months) and 55 typically developing adolescents (27 males, mean age = 151.85 months) participated. They were assessed on the cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 44 publications
5
24
0
Order By: Relevance
“…Besides, evidence from an eight-year, longitudinal study has suggested that phonological awareness provides the basis for the development of morphological awareness in Chinese, which is a better indicator for predicting children’s future reading development [ 40 ]. In addition, studies have revealed that rapid automatized naming deficits play an important role in predicting the incidence of dyslexia [ 35 , 37 ], which is consistent with our results. Rapid automatic naming was strongly associated with early childhood reading skills, and it might be related to speech processing ability and auditory processing impairment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Besides, evidence from an eight-year, longitudinal study has suggested that phonological awareness provides the basis for the development of morphological awareness in Chinese, which is a better indicator for predicting children’s future reading development [ 40 ]. In addition, studies have revealed that rapid automatized naming deficits play an important role in predicting the incidence of dyslexia [ 35 , 37 ], which is consistent with our results. Rapid automatic naming was strongly associated with early childhood reading skills, and it might be related to speech processing ability and auditory processing impairment.…”
Section: Discussionsupporting
confidence: 92%
“…As far as we know, this is the first study to explore the relationship between dyslexia and cognitive-linguistic skills in mainland China. Language processing deficits are commonly reported in dyslexia, including deficits of phonological awareness, morpheme awareness, orthographic awareness, and rapid automatic naming [35][36][37], which is in line with our findings. According to our results, compared with the control group, the scores for rhyme, onset, and tone identification in the dyslexic children were significantly lower.…”
Section: Discussionsupporting
confidence: 92%
“…Children in PE and PB scored consistently lower in Chinese and English vocabulary knowledge than the readers in PC and C. Vocabulary knowledge is another aspect of meaning linked to bidirectional relations of reading acquisition and difficulties (Chung & Lam, 2020; McBride‐Chang et al., 2013). That is, children often learn concepts and use common knowledge during reading, and vocabulary knowledge is important to reading comprehension (Anderson & Freebody, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…As in the phonological awareness tests used in previous studies (Chung & Lam, 2020; Keung & Ho, 2009; Yeung & Ganotice, 2014), a rhyme detection and phoneme deletion task were used. In the rhyme detection task, children were required to listen to 17 items of three monosyllabic rhymes and subsequently indicate which two items sounded similar for each trial.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation